Institutionalised (In)security Exploring the MENA Region's Governance Crises - Cellino, Andrea (ISPI Publications, 2021)
After a decade of popular uprisings and civil wars, the Middle East and North Africa (MENA) region experiences a deep governance crisis. The transformation, weakening or even the collapse of state institutions has changed the security framework, with direct implications for the safety and security of civilian populations across the region. Security Sector Governance and Reform (SSG/R) has to cope with hybridity and institutional fatigue. This report explores the MENA region's governance crises, providing case studies on Libya, Iraq, Tunisia, and Yemen. How can we effectively bring about meaningful SSG/R in hybrid security orders? In which way is "institutionalised insecurity" challenging traditional patterns of governance in vulnerable settings?